Monitoring autophagy in live cells with a fluorescent light-up probe for G-quadruplex structures. Issue 35 (25th March 2019) - Chen, Hongbo; Sun, Hongxia; Zhang, Suge; Yan, Wenpeng; Li, Qian; Guan, Aijiao; Xiang, Junfeng; Liu, Meirong; Tang, Yalin
Abstract : Monitoring autophagy in live cells with a fluorescent light-up probe for G-quadruplex structures. Abstract : Monitoring autophagy can provide valuable insights into understanding human pathological mechanisms, developing novel drugs, and exploring autophagy control approaches. Here, we proposed a new strategy to specifically monitor autophagy by lighting up the G-quadruplex structures entering autolysosomes. Based on this strategy, we designed a small-molecule fluorescent probe for autophagy imaging. This work not only opens up a new way for developing autophagy probes, but also provides an effective tool for autophagy research.